2002
DOI: 10.1152/ajprenal.00037.2002
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of pendrin in intercalated cell subtypes in rat and mouse kidney

Abstract: Recent studies have demonstrated that a novel anion exchanger, pendrin, is expressed in the apical domain of type B intercalated cells in the mammalian collecting duct. The purpose of this study was 1) to determine the expression and distribution of pendrin along the collecting duct and connecting tubule of mouse and rat kidney and establish whether pendrin is expressed in the non-A-non-B intercalated cells and 2) to determine the intracellular localization of pendrin in the different populations of intercalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
165
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(175 citation statements)
references
References 34 publications
9
165
0
1
Order By: Relevance
“…The sections were then rinsed in PBS and mounted with glycerol supplemented with antifading reagent (N-propyl gallate). The microscopy was carried out using a Leica laser confocal microscope (8,17). Immunolabeling controls were performed using antibodies preadsorbed with the immunizing peptide (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…The sections were then rinsed in PBS and mounted with glycerol supplemented with antifading reagent (N-propyl gallate). The microscopy was carried out using a Leica laser confocal microscope (8,17). Immunolabeling controls were performed using antibodies preadsorbed with the immunizing peptide (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Cl Ϫ transport does not occur through principal cells but rather through the paracellular pathway or through the intercalated cells (11). In the B and non-A non-B type intercalated cells, pendrin, an apical anion exchanger (12)(13)(14), is believed to play a key role in BP regulation, most likely by controlling distal nephron chloride reabsorption (15,16). Pendrin is upregulated by the injection of deoxycorticosterone pivalate, a pharmacologic analogue of aldosterone (16).…”
Section: CLmentioning
confidence: 99%
“…2,3,6 Slc26a4 localizes to the apical plasma membrane and apical cytoplasmic vesicles of type B and non-A, non-B intercalated cells within the cortical collecting duct (CCD), the connecting tubule (CNT), the initial collecting tubule (iCT), and the distal convoluted tubule (DCT). 5,7,8 Because Slc26a4 transports HCO 3 Ϫ and participates in bicarbonate secretion by type B intercalated cells, 5,9 previous studies have focused on the role of Slc26a4 in acid-base balance and have shown that Slc26a4 is upregulated in models of metabolic alkalosis. With administration of aldosterone analogues (deoxycorticosterone [DOCP]), Slc26a4 expression is upregulated in tandem with upregulation of apical Cl Ϫ /HCO 3 Ϫ exchange, which increases HCO 3 Ϫ secretion.…”
mentioning
confidence: 99%
“…7,8,15 We have made 2 observations that suggest that the increase in Cl Ϫ absorption by the CCD and CNT following administration of aldosterone analogues is Slc26a4-dependent. 11 First, Slc26a4 is greatly upregulated with DOCP.…”
mentioning
confidence: 99%